Herramientas numéricas para la determinación de curvas de residuo y líneas de univolatilidad (2015)
In this work its present an alternative method for the calculation and determination of residue curve maps and univolatility lines, applied to Acetone-Chloroform-Benzene system. The aim of this method is to minimize the time of calculation needed to generate these tools, more specifically the time required for vapor liquid equilibrium calculations. The method its developed with help of a commercial malingerer like ASPEN PLUS 8.6® and one calculation tool as Excel, the connection of both programs permit to take advantage of the robust calculation solutions of the commercial simulator, using that for generate a simpler alternative in the calculation of the tools mentioned through EXCEL, where can be constructed graphs, as residue curve maps and univolatility lines.